2017
DOI: 10.1189/jlb.5mr0617-257r
|View full text |Cite
|
Sign up to set email alerts
|

Platelets in Wiskott-Aldrich syndrome: Victims or executioners?

Abstract: Microthrombocytopenia is the clinical hallmark of WAS, a rare X-linked immunodeficiency that is characterized by eczema, autoimmunity, and cancer susceptibility. This disease is caused by mutations in the WAS gene, which is expressed in hematopoietic cells and regulates actin cytoskeleton remodeling thereby modulating various cellular functions, including motility, immunologic synapse assembly, and signaling. Despite extensive studies that have provided great insight into the relevance of this molecule to inna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 160 publications
(386 reference statements)
2
16
0
Order By: Relevance
“…Arp2/3 in platelets is activated by NPFs of the WAVE and WASp families, as well as cortactin and HS1 31 , 44 , 62 . Patients with loss-of-function mutations of WASp present with immunodeficiency and bleeding complications, known as Wiskott–Aldrich syndrome 63 . Consequently, it was tempting to speculate whether impaired platelet migration and haptotaxis contribute to the clinical symptoms of WAS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Arp2/3 in platelets is activated by NPFs of the WAVE and WASp families, as well as cortactin and HS1 31 , 44 , 62 . Patients with loss-of-function mutations of WASp present with immunodeficiency and bleeding complications, known as Wiskott–Aldrich syndrome 63 . Consequently, it was tempting to speculate whether impaired platelet migration and haptotaxis contribute to the clinical symptoms of WAS patients.…”
Section: Discussionmentioning
confidence: 99%
“…In Was-deficient mice, platelet turnover was shortened, with proteomic evidence for alterations in proteins of metabolic and proteasomal pathways. 77 Furthermore, in both the mutant mice and patients, there is evidence for a hyperactivation status of the platelets, thus explaining the higher elimination rate. Several groups reported on alterations in integrin activation in the patient's platelets.…”
Section: Wasmentioning
confidence: 99%
“…Several studies have been conducted to elucidate the pathogenesis of thrombocytopenia in patients with WAS. Defective platelet production by megakaryocytes and accelerated peripheral elimination have been proposed as the underlying cause, highlighting an unsolved dichotomy 21 . Megakaryocytes have been described to fail both in the maturation step and in proplatelet production 21 .…”
mentioning
confidence: 99%
“…Defective platelet production by megakaryocytes and accelerated peripheral elimination have been proposed as the underlying cause, highlighting an unsolved dichotomy 21 . Megakaryocytes have been described to fail both in the maturation step and in proplatelet production 21 . Conversely, several articles showed that after normal thrombopoiesis, platelets in the periphery are the target of both innate and adaptive immunity 21 .…”
mentioning
confidence: 99%